Post-pandemic immune profiles: Antibody patterns in vaccinated individuals with and without Prior SARS-CoV-2 infection - Alzahrani, Manar; Alsultan, Afnan; Alamri, Aisha; Aldossary, Rawabi; Yamani, Lamya; Abass, Elfadil (International Journal of Innovative Research and Scientific Studies, 2025)
This study aimed to investigate the serological responses to COVID-19 vaccines in the Saudi population post pandemic, a period characterized by presumed hybrid immunity, and to assess demographic and clinical factors influencing antibody responses. IgG antibody responses to the SARS-CoV-2 spike protein were assessed using chemiluminescent immunoassay (CLIA) in 401 individuals from the Saudi population. Of the 401 participants, 395 were vaccinated and 397 (99%) were positive for anti-SARS-CoV spike protein antibodies, including five of the six unvaccinated individuals. Antibody positivity peaked in ages 20-29 and was lowest in children (0-9 years) and adults over 80 years. IgG levels differed between vaccinated and unvaccinated participants (P < 0.0001) and between sexes (P = 0.0072), but not by vaccine type, dose, or comorbidities. Unexpectedly, vaccinated individuals without prior infection had higher IgG than those with prior infection, challenging the presumed advantage of hybrid immunity. In this Saudi cohort, age and sex significantly influenced spike IgG responses, while vaccine type, dosage, and comorbidities had no effect. Unexpectedly, hybrid immunity showed no advantage, indicating altered immune dynamics at the pandemic’s end. These findings provide valuable insights into population-level COVID-19 immunity and can inform public health strategies and vaccine policies in settings with widespread prior infection or vaccination.